Congenital external hydrocephalus in a dog. (29th April 2019) - Gomes, S. A.; Targett, M.; Lowrie, M.
Abstract : A 4‐year‐old female Chihuahua was presented with progressive seizures, blindness and lethargy. Neurolocalisation was consistent with a diffuse brain lesion affecting the forebrain and cerebellum. MRI demonstrated dilation of the subarachnoid space dorsolaterally surrounding the cerebrum, filled with cerebrospinal fluid (CSF). Ventricular system size was normal, but mild cerebral atrophy was suspected. There was pachymeningeal contrast enhancement, but CSF analysis was unremarkable. This lesion was interpreted to be an external hydrocephalus of suspected congenital origin.